THE PHENOMENON OF ZIKIR SAMAN IN BONJEROK VILLAGE- JONGGAT, CENTRAL LOMBOK WEST NUSA TENGGARA - Atiq, Muhammad (STAI Darul Kamal NW Kembang Kerang, 2020)
This article will discuss the tradition of recitation of zikr Saman in Bonjeruk Village, Central Lombok West Nusa Tenggara. By photographing the phenomenon of the Zikir Saman, this article will review how Zikir Saman implemented in the society by being inspired by hadith texts and along with its acculturation to local culture. By using the living Hadith lens, this research goes through the stages of observation, interview, documentation and interpretation. The identification of problems in this reserach includes: a brief history and development of the zikr saman in Bonjeruk Village, the form of performance and its function in the muslim society. The findings of this study are: First, the tradition of Zikir Saman in Bonjeruk Village has sanad connection to Zikir Saman in Banten which was initiated by Shaykh Abdul Karim. Second, the zikir Saman in Bonjeruk Village experiences dynamics from time to time: from sacred rituals ferformance to profane entertainment show, zikir Saman staged in tourism events. Third, the recitation of Zikr Saman in Bonjeruk Village was a tradition inherent in the aristocracy habitus, because the first bearer of this tradition was Raden Hukum (Datu/King Jonggat). But later, this tradition developed into a folk tradition that most people are interested in.